Amelioration of carbon tetrachloride- and paracetamol-induced hepatotoxicity in rats by Ficus dalhousiae - Ghori, Syed Safiullah; Khan, Mohib; Rahman, Shaikh Abdul (Bangladesh Journal of Pharmacology, 2014)
The present study was undertaken to investigate hepatoprotective activity of Ficus dalhousiae leaves ethanolic extract based on its traditional claim. Paracetamol- and carbon tetrachloride-induced hepatotoxicity in albino Wistar rats, experimental models was used for the evaluation. Various biochemical parameters like SGPT, SGOT, serum albumin, alkaline phosphatase, total bilirubin, direct bilirubin and total protein were estimated. Oral treatment with the extract 250 and 500 mg/kg, significantly (p<0.01) altered all the serum marker levels to the normal in both the experimental models. The activity of the extract was comparable to that of standard drug, silymarin (25 mg/kg, p.o.). Histopathological observations also demonstrated protective effect of the test extract on liver anatomy. Overall results suggest that F. dalhousiae possesses in vivo hepatoprotective activity.